Psychometric analysis of the critical thinking skills instrument in physics learning using the Rasch model - Noperi, Hendri; Diani, Rahma; Irwandani, Irwandani; Suryani, Yani; Sodikin, Sodikin; Saputro, Trimo (Universitas Islam Negeri Raden Intan Lampung, 2025)
Critical thinking is a core competency in physics learning, yet measuring it is constrained by a lack of psychometrically validated instruments. This study aims to develop and analyze a critical thinking assessment instrument on